Gabon : Financial System Stability Assessment, Including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Insurance Regulation. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of the Financial System Stability Assessment for Gabon, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Insurance Regulation. The assessment reveals that the Gabonese financial sector is dominated by a relatively sound but small banking sector that focuses squarely on the formal sector. The operating environment is characterized by a fixed peg to the euro, heavy dependence on oil exports, and continued government presence in both the enterprise and financial sectors.